Problematics of Improving Fine Motor Abilities of Children Age 5-6 Years - Isnaini, Rizki; Katoningsih, Sri (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2021)
Fine motor skills are an aspect of development that is emphasized in early childhood education. AbilityFine motor skills are developed from an early age in order to have the skills to coordinate the eye and hand. The research objective is to examine the literature, articles and research documents that identify problems in improving fine motor skills of early childhood. Methods: references in the form of primary articles of approximately 20 articles 15 national journals with a period of 5 years and international journals with a period of 7 years with accredited quality and reputation. This research uses qualitative research with literature review method. The samples of this research are: 1) Related to fine motoric development of early childhood, 2) Respondents are early childhood, 3) The independent variable is problematics and the dependent variable is fine motor skills, 4) The treatment given is a problem which can improve fine motor skills. Results and discussion: The Literature Review states that media can affect fine motor skills, including pencil shavings collage,constructive play with paper, unit beam, playdough, kirigami. method can have an effect on improving fine motor skills, that isu aquatic / water learning, cutting activities, collage activities, cutting and pasting activities, demonstration methods, printing activities using banana leaves, coloring pictures, practical life in montessori education, interactive writing. There are several factors that can affect the improvement of fine motor skills, namely counseling through play activities, learning plans, learning preparation, learning environment, being overweight, and motivation.. Conclusion: learning media, learning methods are problems that do not dominate, but there are other factors that are problematic in improving fine motor skills, including counseling through play activities, lesson plans, learning preparation, learning environment, overweight, and motivation.